The Social Validity of Orðaheimurinn for Supporting Multilingual Children’s Icelandic Vocabulary Development: Perspectives from Teachers and Directors. „This is just a language stimulant on a silver platter. You don’t need anything more, just off you go“ - Hanna Einarsdóttir 1990- (2024)
Some preschool-aged children in Iceland face challenges in acquiring age-appropriate Icelandic language skills, attributed to developmental language disorder, speech sound disorder or the complexities of multilingual language acquisition. The results of previous research have consistently demonstrated significantly weaker Icelandic skills in multilingual children compared to their monolingual peers, necessitating evidence-based and socially valid interventions to enhance language and vocabulary development. Interventions need to have been demonstrated to be both effective and socially valid in order to inform the evidence base for practice. Social validity describes the extent to which an intervention is socially accepted, or valued, by its users (Kazdin, 1977; Wolf, 1978). Social validity encompasses three essential elements. Firstly, the goal examines the extent to which the intervention's aims are valued by users, determining whether the changes brought about are important and should be a priority for those affected. Secondly, the procedure assesses whether the intervention's implementation is appropriate and acceptable to users, focusing on its feasibility within the preschool setting. Lastly, the effect evaluates user satisfaction with observed effects, determining whether users believe the intervention works and achieves the desired outcome. Orðaheimurinn (OH) is a language stimulation intervention which is based on World of Words (WOW: Neuman et al., 2021). The study described in this thesis describes research into the social validity of OH. A cluster randomised controlled trial (CRCT) was conducted to investigate the effectiveness of OH. This intervention was implemented by teachers and tested in five Icelandic preschools. OH utilized shared book reading experiences within a soft-scripted approach designed to increase children’s vocabulary knowledge and depth. Assessment of social validity in this study involved surveys and interviews with the teachers implementing OH and the preschool directors at the ...